Recent Advances in Metal-Containing Polymer Hydrogels - Li, Hui (Macromol Rapid Commun, 2017)
Metal-containing polymer hydrogels have attracted increasing interest in recent years due to their outstanding properties such as biocompatibility, recoverability, self-healing, and/or redox activity. In this short review, methods for the preparation of metal-containing polymer hydrogels are introduced and an overview of these hydrogels with various functionalities is given. It is hoped that this short update can stimulate innovative ideas to promote the research of metal-containing hydrogels in the communities.